Isolation and sequence analysis of peptides from the venom of Protonectarina sylveirae (hymenoptera‐vespidae) - Dohtsu, Kunihiko; Okumura, Kaoru; Hagiwara, Ken'Ichi; Palma, Mario Sergio [UNESP]; Nakajima, Terumi (My University, 1993)
Three new venom peptides were isolated from the Brazilian wasp; Protonectarina sylveirae and their complete amino acid sequences were determined by Edman degradation as well as by FAB‐mass spectrometry. One (P‐8) of them was a new analog of mastoparan family; therefore, we named it Protonectarina mastoparan. Another peptide (P‐10) had an amino acid sequence homolosy with Ves‐CP‐T, a chemotactic peptide of wasp venom, and bombolitin‐V, the venom peptide from bumblebee. The third peptide (P‐6) was structurally unique, possessing an intramolecular disulfide bond. Not only Protonectarina mastoparan (P‐8) but also P‐6 and P‐10 caused histamine release from rat peritoneal mast cells as potently as mastoparan (EC50 s were about 1 × 10−6 M for P‐6 and 2 × 10−6 M for P‐10). In addition, P‐10 in a concentration higher than 1 × 10−5 M induced hemolysis though whose hemolytic activity was about a half potency of that of mastoparan. However, P‐6 did not cause hemolysis up to the concentration of 10μM. We have named them sylverin for the peptide P‐6 and protonectin for the peptide P‐10. © 1992 Wiley‐Liss, Inc. Copyright © 1993 Wiley‐Liss, Inc., A Wiley Company
Keywords: Histamine; Mast cell; Mastoparan; Peptide; Protonectin; Sylverin; Venom; Wasp